Development Of Si02 Thin Film On singlecrystal Sic By anodic oxidation technique. - Cheong, Kuan Yew; Purwadaria, Sunara; Lockman, Zainovia (Universiti Sains Malaysia, 2008)

(untitled)
Anodic silicon dioxide (Si02) thin film is growth on p- and n-type silicon (Si) and p-type 4H-silicon carbide (SiC) substrate with the thickness ranging from 50-130 nm.